The State's Responsibility in Protecting Children in Online Schools during the Covid-19 Pandemic - Dewi Bunga (Fakultas Hukum Universitas Muhammadiyah Magelang, 2021)
The number of violence against children seen increases during Covid-19 pandemic, which requires the students to carry out learning activities remotely. This condition causes children to feel burdened, often the parents feel the impact, while they have routine tasks and work. This condition causes parents abuse their children, both physically and psychologically. The purpose of this study is to analyze the recent Indonesian Government policy regarding the fulfillment of children's rights especially on the online learning process during the pandemic. This study used normative legal research with statute approach. The results shows that the state has an obligation to protect children from violence which set out through penal and non-penal policies. However, penal policies that imposed to the parents and teachers are inappropriate rather than implementing the preventing action (non-penal policies). Lastly, psychological counselling provided by the government and psychological consultant needs to be given regularly to the teachers and parents as a better solution to tackle the issues.